Fenomena Penggunaan Bahasa Pegon dalam Meningkatkan Pemahaman Kitab Kuning di Pondok Pesantren Darussalam Putri Utara Blokagung Banyuwangi - Olivia Anggreany; Manshur, Ali Manshur (IAI Darussalam, 2024)
Darussalam Blokagung Islamic Boarding School is an Islamic educational institution that has certain characteristics, the most famous in Banyuwangi. Although when observed closely, the students at the Darussalam Putri Utara Islamic Boarding School have various backgrounds from their regions, but are able to understand the yellow book literature which only has one language, namely pegon Arabic.This research aims to: 1) describe the use of pegon language in understanding the Yellow Book, and 2) describe the factors that influence the use of pegon language in understanding the meaning of the Yellow Book. This research method is a qualitative type of phenomenology. Through this approach, the data sources used use primary data and secondary data where research is carried out directly through primary sources and document collection as the main media. Data collection techniques in this research used observation, data collection by interviews, and documentation. The results of this research show that the use of the Pegon language is an important component in learning the Yellow Book at the Darussalam Putri Utara Islamic Boarding School, Blokagung Banyuwangi, and plays an important role in facilitating students' understanding of the text. And there are potential factors that can influence students' understanding as follows: 1) Quality of teaching, 2) Availability of resources and references, 3) Peer support and discussion, 4) Cultural and linguistic background, 5) and the role of Indonesian as a unifier in learning yellow book.